A primary care update to circumcision. Issue 3 (March 2020) - Osinibi, Elizabeth; Smith, Thomas; Henderson, Alastair
Male circumcision is the oldest and most commonly performed surgical procedure, worldwide. Historically, it has largely been performed for ritual and religious indications. However, in the last few decades, its practice, which was once taken up for non-medically proposed health benefits, has now become increasingly controversial in Europe. This article aims to highlight the clinically acceptable indications for circumcision in the UK. It discusses the assessment of a patient with phimosis, and alternatives that may be attempted in primary care before referral to a surgeon. It also aims to summarise the controversy and potential complications of circumcision, which patients may wish to consider prior to referral.